Authentic Tasks to Foster Oral Production Among English as a Foreign Language Learners - Sandra Milena Ramírez Ortiz; Marco Tulio Artunduaga Cuéllar (Asociación Colombiana de Profesores de Ingles, 2018)
Attaining oral production is a challenge for most English language teachers because most of the strategies implemented in class do not engage students in speaking activities. Tasks are an optimal alternative to engage learners in communicative exchanges. This article presents the results of a qualitative action research study examining the effects of authentic tasks in oral production with a group of tenth graders in a public high school in the south of Colombia. Considering the conclusions of the study teachers are encouraged to use authentic tasks in the classroom to involve students in meaningful learning to foster oral production.